Gingival Bleeding and Bloody Dialysate: A Case Report of Scurvy in a Child With End-Stage Renal Disease Receiving Peritoneal Dialysis - Kulnipa Kittisakmontri (2018)
© 2016 National Kidney Foundation, Inc. Patients with chronic kidney disease (CKD) or end-stage renal disease are at risk for vitamin C deficiency and scurvy due to diet restriction, increased urinary loss of the water-soluble vitamin C with diuretics, and in case of patients who are on dialysis, through dialysates. The condition may be overlooked as the clinical manifestation of scurvy may be subtle, and some presentations may mimic clinical signs in CKD. We reported a case of scurvy presenting with gingival bleeding and blood dialysate in a 6-year-old girl with end-stage renal disease who was on continuous ambulatory peritoneal dialysis. Physical examination showed gingival hyperplasia and bleeding, and the pathognomonic bleeding of perifollicular hemorrhage. The typical radiographic changes were present. The clinical signs and symptoms resolved after ascorbic acid treatment. This case underscores the importance of awareness of the increased risk for vitamin C deficiency in patients with CKD and receiving dialysis.